From Generation Z to Generation Alpha: An Analysis of Linguistic Registers - CAPELLAN, KATLEEN JOY; Tarun, Jaine (International Journal of Arts, Sciences and Education, 2026)
This research aims to examine the rapid transformation and development of the Filipino language by analyzing the corpus registers utilized by Generation Z and Generation Alpha. Amid accelerated digitalization and globalization, novel forms of speech emerge, reflecting the distinct sociolect and idiolect characteristics of contemporary youth. The study employed descriptive research design and corpus linguistics to identify the frequently used registers of Gen Z and Gen Alpha. Through a questionnaire validated by the research adviser and members of the panel of examiners, interviews were conducted with fourteen students belonging to the Gen Z and Gen Alpha cohorts. Following the interviews, the researcher utilized Content Analysis and Linguistic Analysis to examine the gathered data. Based on the data collected from actual interviews and discourse, the morphological and semantic characteristics of the words were analyzed. The study emphasizes that the acceptance of modern registers does not degrade the language; rather, it serves as evidence of the dynamic and progressive nature of the Filipino language. The output of this study is expected to assist educators, linguists, and translators in understanding the contemporary discourse of Filipino youth.